PET imaging of dopamine release in the frontal cortex of manganese‐exposed non‐human primates. Issue 2 (26th March 2019) - Guilarte, Tomas R.; Yeh, Chien‐Lin; McGlothan, Jennifer L.; Perez, Juan; Finley, Paige; Zhou, Yun; Wong, Dean F.; Dydak, Ulrike; Schneider, Jay S.
Abstract: Humans and non‐human primates exposed to excess levels of manganese (Mn) exhibit deficits in working memory and attention. Frontal cortex and fronto‐striatal networks are implicated in working memory and these circuits rely on dopamine for optimal performance. Here, we aimed to determine if chronic Mn exposure alters in vivo dopamine release (DAR) in the frontal cortex of non‐human primates. We used [ 11 C]‐FLB457 positron emission tomography with amphetamine challenge to measure DAR in Cynomolgus macaques . Animals received [ 11 C]‐FLB457 positron emission tomography scans with and without amphetamine challenge prior to Mn exposure (baseline), at different time points during the Mn exposure period, and after 10 months of Mn exposure cessation. Four of six Mn‐exposed animals expressed significant impairment of frontal cortex in vivo DAR relative to baseline. One Mn animal had no change in DAR and another Mn animal expressed increased DAR relative to baseline. In the reversal studies, one Mn‐exposed animal exhibited complete recovery of DAR while the second animal had partial recovery. In both animals, frontal cortex Mn concentrations normalized after 10 months of exposure cessation based on T1‐weighted magnetic resonance imaging. D1‐dopamine receptor (D1R) autoradiography in frontal cortex tissue indicates that Mn animals that experienced cessation of Mn exposure expressed D1R levels that were approximately 50% lower than Mn animals that did not experience cessation of Mn exposure or control animals. The present study provides evidence of Mn‐induced alterations in frontal cortex DAR and D1R that may be associated with working memory and attention deficits observed in Mn‐exposed subjects. Abstract : Humans exposed to excess levels of manganese (Mn) exhibit deficits in working memory and attention. Using [ 11 C]‐FLB457 PET with amphetamine (AMPH) challenge we measured in vivo dopamine release in the frontal cortex of non‐human primates chronically exposed to Mn. We found that Mn exposure inhibits in vivo dopamine release in the frontal cortex and this effect was associated with working memory and attention deficits in Mn‐exposed animals. The inhibition of frontal cortex dopamine release and behavioral deficits is not associated with blood Mn concentrations, but appears to be modulated by the level of Mn accumulation in the frontal cortex measured by T1‐weighted MRI.